(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The SIRIA Project, developed as part of a strategic project leaded by the Department of Archeology of the University of Bologna, is a centralized system for management, research and presentation of the archaeological record. The system is capable of managing within a relational database the main information classes generated by archaeological research: alphanumeric-tabular data, spatial data and images (and generally all kinds of files that needed to be stored). The database’s architecture, developed in a flexible way, allows users to set, on a common structure, specific information groups (plug-ins). The goal is to ensure the coexistence of single individual’s needs to freely organize their data in a functional manner to their researches and the disciplinary exigency to integrate data and perform analysis at scales greater than those of individual projects. The SIRIA Project joins the philosophy and the aims of the open source movement: the code is released under the GPLv3 free software license.